Villa Tolstoy – The architecture of balance and spatial consistency - Milutinovic, Predrag (Arhitektura i urbanizam, 2025)
Villa TLS, located in Tolstoy Street, Belgrade, is a refined example of a contemporary urban villa that thoughtfully integrates function, context, and aesthetics. Designed by architect Predrag Milutinović and MAPA Architects, the project is based on clear spatial and typological organisation, emphasising balance between public and private, solid and transparent. The stone façade, accentuated with metal details, introduces tactility and a sense of permanence, while the treatment of light enriches the spatial experience. Advanced technical systems and ecological features are seamlessly incorporated. Villa TLS affirms that architecture can be both rooted in a local context and relevant on a global scale.
Keywords: contemporary villa; architecture of balance; materiality; spatial typology; urban context